Utility of PLUS CYCLE to measure physical activity and sleep duration and detect postoperative sleep disturbances in hospitalized dogs - Akihiro Ohnishi; Makoto Yamamoto; Natsuki Akashi; Eri Iwata; Taketoshi Asanuma; Yoshiki Itoh (PLoS ONE, 2025)
Sleep is essential for animal health and welfare. In humans, postsurgical sleep disturbances can delay postoperative recovery. However, objective sleep evaluation in dogs and studies of postoperative sleep disturbances in animals have not been reported. This study aimed to determine whether activity monitors (PLUS CYCLE®; JARMeC, Kanagawa, Japan) can accurately monitor the condition of hospitalized dogs and postoperative sleep disturbances. First, the activity data collected by PLUS CYCLE® were compared with the observation data in a video of hospitalized dogs (n = 9). We determined the correlation between the total hours of physical activity, Sleeping/Resting time and amount of physical activity collected by PLUS CYCLE®, and the time when body movements could not be confirmed (inactive time) recorded by video. There was a strong correlation between the inactive time observed in the videos and the Sleeping/Resting time in PLUS CYCLE® (p < 0.0001, r = 0.95). Thereafter, six hospitalized dogs (n = 6) that underwent phacoemulsification and aspiration surgery for cataracts at the Veterinary Teaching Hospital of the Okayama University of Science were monitored to compare pre- and postoperative amounts of physical activity and Sleeping/Resting time between two groups: the Colorado State University Acute Pain Scale (APS) = 0 group (n = 3) and the APS = 1 group (n = 3). A significant decrease in postoperative sleep duration was observed in the APS = 1 group (p = 0.0224). This prospective study suggested that PLUS CYCLE® can accurately assess the condition of hospitalized dogs and that it has the potential to detect postoperative sleep disturbance. Thus, PLUS CYCLE® may help manage postoperative hospitalization and pain management.